Treatment outcome of prepubertal gonadal tumors: The Children’s Hospital Lahore Pakistan experience - Ahmad, Alia; Saleem, Mohammad; Khan, Fauzia Shafi (Journal of Fatima Jinnah Medical University, 2019)
Background: Prepubertal gonadal terms are rare with an incidence of 0.5-2 per 100,000 populations. Due to their rare occurrence, their presentation and management have not been established. This study aims to highlight the clinical and histopathological features of prepubertal gonadal tumors along with treatment outcome at a tertiary care specialist hospital in Central Punjab. Patients and methods: Records of Hospital Lahore Pakistan from January 2011 to December 2017 were retrospectively reviewed. Histopathological features, risk stratification, clinical stages, and their outcomes were analyzed. Demographic details, histopathological features, risk stratification (high risk with serum alpha protein (AFP) more than 10,000ng/ml, thoracic tumor and stage IV at presentation), clinical stages at presentation using TNM clinical and post-surgical classification and Oncology Group staging system (COG), and their treatment outcomes were analyzed. The United Kingdom protocol consisting of Carboplatin, Etoposide and Bleomycin (JEB) chemotherapy was used for treatment. Results: Out of 105 patients, 69% were females and 41% were less than 5 years of age. Only 6% tumors were benign whereas 94% were malignant. Among them 92 (88%) patients had tumor size more than 5cm. Among total 70% were categorized as high-risk. On histopathology, 49% were yolk sac tumors, 12% were mixed malignant germ cell tumor, 12% dysgerminoma, 8% teratomas, 5% juvenile granulose cell tumor, 2% Sertoli and Leydig cell tumors and rest were unspecified. Out of 105 patients, 16% had stage II, 40% stage III and 44% stage IV at presentation. Orchidectomies and Oosalpingectomies were undertaken in 80% cases. Multidisciplinary team management (MDT) was utilized in 67% cases. Among them 72% completed treatment and were well while 8% abandoned treatment. There were overall 18% deaths, 79% due to disease progression and advanced stage of the disease with delayed treatment and 21% due to infection. Febrile neutropenia was the commonest event during treatment observed in 29% patients followed by obstructive uropathy in 13% patients. Tumor local recurrence following surgery was noted in 10% cases. Conclusions: Majority of the prepubertal gonadal tumors was malignant, commonest histopathological sub-type being Yolk Sac tumor followed by dysgerminoma. High mortality and treatment abandonment can be reduced by timely diagnosis and efficient multidisciplinary team management to achieve cure rates being obtained in developed countries.